Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s42358-018-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis in 847 childhood-onset systemic lupus erythematosus population: a multicentric cohort study

Abstract: Objective: To evaluate autoimmune hepatitis (AIH) in a multicenter cohort of childhood-onset systemic lupus erythematosus (cSLE) patients. Methods: This retrospective multicenter study included 847 patients with cSLE, performed in 10 Pediatric Rheumatology services of São Paulo state, Brazil. AIH was defined according to the International Autoimmune Hepatitis Group criteria (IAHGC). The statistical analysis was performed using the Bonferroni's correction (p < 0.0033). Results: AIH in cSLE patients confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The reveal prevalence of overlapping SLE and AIH still remained unknown. Balbi et al (15) reported in multicenter cohort study that AIH in pediatric SLE patients confirmed by biopsy was observed in 7/847 (0.8%) and all were diagnosed during adolescence. The majority occurred before or at SLE diagnosis [5/7 (71%)].…”
Section: Discussionmentioning
confidence: 99%
“…The reveal prevalence of overlapping SLE and AIH still remained unknown. Balbi et al (15) reported in multicenter cohort study that AIH in pediatric SLE patients confirmed by biopsy was observed in 7/847 (0.8%) and all were diagnosed during adolescence. The majority occurred before or at SLE diagnosis [5/7 (71%)].…”
Section: Discussionmentioning
confidence: 99%
“…[19,28,29] SMA are typically of IgG subtype and thus can theoretically cross the placenta just like SSA/SSB, however, only 20-60% of NLE mothers have a history of an autoimmune disorder, mainly lupus, which can rarely be associated with AIH-1. [5,30] Thus the finding from our case deserves to be highlighted. Nevertheless, we believe that SMA presence in our patient was due to a false-positive reaction rather than a true early onset AIH-1, especially given the patient's complete resolution of liver injury while being off-immunosuppression.…”
Section: Discussionmentioning
confidence: 58%
“…Some of these children will go on to develop SLE, others will develop other rheumatic diseases, and some will remain asymptomatic. 10 SLE typically presents with a variety of complications, such as vascular, cardiac, nervous system, pulmonary, and renal involvement, as well as positive ANA and or patients with seronegative ANA tests have a higher prevalence of positive Ro factor antibody. However, there were no further systemic symptoms or the presence of these antibodies in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these children will go on to develop SLE, others will develop other rheumatic diseases, and some will remain asymptomatic. 10 …”
Section: Discussionmentioning
confidence: 99%